Prevalence and Antibiogram of Acinetobacter Species Isolated from Various Clinical Samples in a Tertiary Care Hospital - Rajkumari, Sanjana; Pradhan, Shanti; Sharma, Damodar; Jha, Brajesh (Journal of College of Medical Sciences-Nepal, 2020)
Background: Acinetobacter species has emerged as a significant hospital pathogen, and are becoming increasingly drug resistance. They cause outbreaks in intensive care units and health care units. Methods: A cross-sectional study was conducted to determine the prevalence and antibiotic susceptibility pattern of Acinetobacter spp isolated from various clinical samples collected from patients admitted in various wards and intensive care units of the hospital over a period of one year (March 2018 to Feb 2019). Results: Out of 2,623 samples, 1,201(45.78%) yielded significant growth and out of these positive cultures, 138(11.49%) Acinetobacter spp were isolated. Majority of isolates 24(17.39%) were isolated from General intensive care unit (GICU). Maximum sensitivity of Acinetobacter spp was seen towards polymyxin B 138(100%) and colistin 138(100%), followed by tigecycline 127(92.02%). Hundred and one (80.43%) isolates were found to be multidrug resistant. Conclusions: Acinetobacter isolates showed multidrug resistant pattern mostly in inpatients. To avoid resistance, antibiotics should be used judiciously. There is also an urgent need for emphasizing the importance of hand washing and use of disinfectants in prevention of transmission of infection in health care setup. Keywords: Acinetobacter spp; prevalence; antibiotic resistance; intensive care units; multidrug resistance.